2018
DOI: 10.5249/jivr.v10i2.980
|View full text |Cite
|
Sign up to set email alerts
|

Frequency of complications of falling from the walnut tree, as an occupational-seasonal injury

Abstract: Abstract:Background:Falling from a tree is one of the major causes of serious injuries in farmers but it can be prevented. Walnut is one of the most important agricultural products in Iran and falling from walnut trees is common during the season of harvest. The aim of this study was to determine the frequency of complications due to falling from walnut tree in patients referred to the emergency department of Imam Ali Hospital in Bojnurd City, Iran.Methods:A descriptive cross sectional study was conducted on 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 14 publications
2
2
0
Order By: Relevance
“…It was shown that farmers and farmworkers who have experienced health problems are more susceptible to falling from the trees (15). Similar to another study (16), the results of this study demonstrated that falling from walnut trees affected aging individuals who climbed the trees to harvest. Aging males who climb trees may be less cautious and more likely to have chronic diseases that affect their balance and physical condition due to their age.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…It was shown that farmers and farmworkers who have experienced health problems are more susceptible to falling from the trees (15). Similar to another study (16), the results of this study demonstrated that falling from walnut trees affected aging individuals who climbed the trees to harvest. Aging males who climb trees may be less cautious and more likely to have chronic diseases that affect their balance and physical condition due to their age.…”
Section: Discussionsupporting
confidence: 86%
“…Similar to another study in Iran (16), breaking branches was the main reason for falls in participants. Aging and diseases were the main causes of falling from other fruit trees (21).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations